EFFECTS OF FEEDING FREQUENCY ON SOME PHYSIOBIOLOGICAL PARAMETERS OF COMMON CARP (Cyprinus carpio) - Nasreen M. Abdulrahman; Sarwar A. Hama Amin; Vian M. Ahmed; Hawkar J. H. Ameen; Bakhan R. Hassan (Basrah Journal of Veterinary Research)
In present study the effect of feeding frequency on some health aspects (biologicalparameters) of fingerling of common carp were investigated. Three groups of common carp(average weight4.31±0.1 g) designed with three feeding frequencies one meal a day (D1),two meals a day (D2) and three meals a day (D3) with three replicates of each treatment. Fishin experimental treatments were fed by 4% of body weight. No significant differencesobserved in Hepatosomatic Index, Gill Index and muscle ratio (Weight without Viscera andWeight without Viscera & Head) in all feeding frequencies, feeding one and two time perday were significantly higher than three times/ day in each of Kidney index and SpleenIndex. Intestine weight index was significantly higher in T2 and T3, Intestine Length Indexwas higher significantly in T3.